Numerical investigation of hypersonic flow with repetitive-pulsed plasma actuators. (July 2018) - Wang, Chin-Cheng; Hsu, Li-Chung
Repetitive-pulsed plasma actuators have become the key enabler for flights in the hypersonic flow control. A numerical study focuses on the effect of the repetitive-pulsed plasma actuators at Mach 6. The geometric effects of circular, square, and triangular cylinders as well as a sphere on the aerodynamic performance are considered in the present study. For flow over the circular cylinder and sphere, shock control by repetitive-pulsed discharges is investigated, respectively. The baseline results are successfully validated with the theoretical and published numerical values for flow past a circular cylinder at Mach 6. Without flow control, results show that the shapes of the triangular cylinder and sphere have much smaller high-pressure regions compared to that of the square and circular cylinders. With repetitive-pulsed plasma, the time-average drag reduction has been reduced by a maximum of 0.8% and the stagnation pressure ratio is reduced by 2.1% for Mach 6 flow over a circular cylinder. Thus, this research shows a great benefit of repetitive-pulsed discharges to the state-of-the-art in high-speed flight design.